Genetic transformation in Staphylococcus aureus: demonstration of a competence-conferring factor of bacteriophage origin in bacteriophage 80 alpha lysates. - Thompson, N E (1981)
A virion component that is responsible for conferring competence to Staphylococcus aureus was demonstrated in lysates of bacteriophage 80 alpha, a serological group B phage. Isolated particles of 80 alpha could not be shown to confer significant levels of competence. The phage component had a density of about 1.3 g/cm3, was inactivated by pronase, and was inhibited by antiserum prepared against isolated infectious particles of a serological group B phage. Centrifugation through a Ficoll gradient resulted in separation of competence-conferring activity and plaque-forming units. It is concluded that this proteinaceous subvirion component constitutes a bona fide competence factor of bacteriophage origin.